Performance of quality protein maize (Zea mays L.) varieties at varying fertility levels - ., Snehlata; Singh, Dilip; Nepalia, V. (Annals of Agricultural Research, 2016)
Field experiment was conducted during kharif 2014 to evaluate performance of quality protein maizehybrids under fertility levels. Treatment consisted quality protein maize varieties viz., HQPM 1,HQPM 5, Pratap QPM hybrid 1 and Vivek QPM 9 and four fertility levels viz., 90 + 12.9, 110 + 17.2,130 + 21.5 and 150 + 25.8 kg N + P ha–1. Highest values of yield attributing parameters, grain (4.26t ha–1), stover yield (6.33 t ha–1), net return (45176 ` ha–1and B C ratio (2.42) were obtained withHQPM 1. Similarly total N P K uptakes were significantly higher in HQPM 1 over rest of the varieties.Protein content of HQPM 1, HQPM-5 and Pratap QPM 1 were statistically at par but significantlyhigher than Vivek QPM 9. At harvest experimental soil with Vivek QPM 9 had significantly higherN and P however, K status of soil did not vary significantly. For quality protein maize, applicationof 150 kg N + 25.8 kg P ha–1 significantly improved growth, yield attributing parameters, grain (4.17t ha–1) and stover (6.25 t ha–1) yield and proved economically profitable dose with highest net returns(43302 ` ha–1) and BC ratio (2.25).